The Saviour Shoe - S.O.S Sdn Bhd / Nureen Farahiyah Mat Said - Mat Said, Nureen Farahiyah (2020)
The company was named as S.O.S SDN BHD is partnership business that supplied the safety shoe called the Saviour Shoe. S.O.S SDN BHD aims to be the most competitive and reliable company in provide technological shoe. Our business concept is basically to provide shoe with technology devices that mainly focus on safety of people nowadays. The concept of the saviour shoe are to reduce the risk of crime happened to people’s nowadays while improve the quality of life by providing them one step ahead of security. The Saviour Shoe used the elements of product concept such as usability by providing wireless charging to improve the productivity of usage of the shoe. The price concept of the shoe is based on “affordable- luxury” concept which offered device technology in the shoe with affordable and reasonable price while at the same time providing people the best quality and functionality of the shoe.